2013
DOI: 10.1200/jco.2013.31.15_suppl.3019
|View full text |Cite
|
Sign up to set email alerts
|

Nonclinical evaluation of the combination of mouse IL-21 and anti- mouse CTLA-4 or PD-1 blocking antibodies in mouse tumor models.

Abstract: 3019 Background: Interleukin 21 (IL-21), a γc chain family cytokine, is produced primarily by CD4+ T cells and has many effects on immune cells, including enhancing CD8+ T cell and NK cell proliferation and cytotoxicity. Recombinant IL-21 (rIL-21) therapy resulted in objective responses in ~20% of melanoma and renal cell carcinoma patients. In mouse models, monoclonal antibody (mAb) blockade of CTLA-4 prolongs antigen-specific T cell responses, while blockade of programmed death 1 (PD-1) reverses tumor induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For instance, combination of cytotoxic T‐lymphocyte‐associated antigen 4 inhibitor and PD‐1 inhibitor raises the antitumor activity compared with each regimen alone (Curran et al, ; Selby et al, ); and lymphocyte activation gene‐3 inhibitor plus PD‐1 inhibitor illustrate good efficacy in treating established tumors, which are resistant to each single inhibitor treatment (Woo et al, ). Similarly, PD‐1 inhibitor improves the antitumor activity of recombinant interleukin (IL)‐21 with strong tumor growth inhibition and complete regression in the majority of cancer mice (Jurekunkel et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, combination of cytotoxic T‐lymphocyte‐associated antigen 4 inhibitor and PD‐1 inhibitor raises the antitumor activity compared with each regimen alone (Curran et al, ; Selby et al, ); and lymphocyte activation gene‐3 inhibitor plus PD‐1 inhibitor illustrate good efficacy in treating established tumors, which are resistant to each single inhibitor treatment (Woo et al, ). Similarly, PD‐1 inhibitor improves the antitumor activity of recombinant interleukin (IL)‐21 with strong tumor growth inhibition and complete regression in the majority of cancer mice (Jurekunkel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences have verified that the PD‐1 pathway is closely involved in tumor immune evasion, and tumor cells with upregulated PD‐1/PD‐L1 show increased resistance to T‐cell‐mediate lysis and exhibit elevated tumorigenesis as well as invasiveness compared to tumor cells with downregulated PD‐L1 expression, indicating blockade of the PD‐1 pathway would restore antitumor immune responses in cancers (Iwai et al, ; Iwai, Terawaki, & Honjo, ). Most importantly, blockade of PD‐1 pathway is widely discovered to enhance the antitumor effect of other immunotherapeutic approaches (Curran, Montalvo, Yagita, & Allison, ; Jurekunkel et al, ; Selby et al, ; Woo et al, ). For instance, combination of cytotoxic T‐lymphocyte‐associated antigen 4 inhibitor and PD‐1 inhibitor raises the antitumor activity compared with each regimen alone (Curran et al, ; Selby et al, ); and lymphocyte activation gene‐3 inhibitor plus PD‐1 inhibitor illustrate good efficacy in treating established tumors, which are resistant to each single inhibitor treatment (Woo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nivolumab reportedly promotes the antitumor effect of several other immunotherapeutics; for instance, a previous study revealed a synergistic effect between nivolumab and a cytotoxic T lymphocyte-associated antigen four blockade (9D9) (another representative first-generation four immune checkpoint inhibitor) in melanoma treatment ( 45 ). Another study illustrated that nivolumab enhances the antitumor effect of recombinant IL-21 in several cancer mouse models ( 46 ). Based on the data above, it was hypothesized that nivolumab could improve the cytotoxic activity of OCT4&SOX2 CTLs towards BCSCs.…”
Section: Discussionmentioning
confidence: 99%